2019
DOI: 10.1002/art.40913
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Adenosine Deaminase 2 Gene Variants and Varied Clinical Phenotype in Pediatric Vasculitis

Abstract: Objective Individuals with deficiency of adenosine deaminase 2 (DADA2), a recently recognized autosomal recessive disease, present with various systemic vascular and inflammatory manifestations, often with young age at disease onset or with early onset of recurrent strokes. Their clinical features and histologic findings overlap with those of childhood‐onset polyarteritis nodosa (PAN), a primary “idiopathic” systemic vasculitis. Despite similar clinical presentation, individuals with DADA2 may respond better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 20 publications
5
70
0
Order By: Relevance
“…in two patients carrying a homozygous deletion of the locus 22q11.1, harboring both copies of the il-17 receptor a (IL17RA) and the CECR1 gene, muco-cutaneous infections and dermatitis were observed (26). By contrast, Gibson et al (18) were not able to correlate genotype to phenotype in nine children diagnosed with dada2, thus assuming that apart from the ada2 mutations other factors such as modifying genes, epigenetic modifications and possibly environmental factors are also involved in the pathogenesis of dada2 and disease expressivity. Therefore, further studies are warranted in order to better understand the genotype-phenotype correlation in patients with dada2.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…in two patients carrying a homozygous deletion of the locus 22q11.1, harboring both copies of the il-17 receptor a (IL17RA) and the CECR1 gene, muco-cutaneous infections and dermatitis were observed (26). By contrast, Gibson et al (18) were not able to correlate genotype to phenotype in nine children diagnosed with dada2, thus assuming that apart from the ada2 mutations other factors such as modifying genes, epigenetic modifications and possibly environmental factors are also involved in the pathogenesis of dada2 and disease expressivity. Therefore, further studies are warranted in order to better understand the genotype-phenotype correlation in patients with dada2.…”
Section: Discussionmentioning
confidence: 95%
“…However, the disease severity was found to be highly varied from mild type of the disease limited to the skin, without any constitutional symptoms to severe, which was finally fatal in some cases (1). As regards the study conducted by Gibson et al (18), the authors suggested that arg8Trp may have benign consequences and both leu351Gln and ala357Thr probably damaging ones. It has been suggested that the clinical significance of novel variants cannot be assessed from their allele frequencies only (21).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations